1984
DOI: 10.1152/ajpgi.1984.247.6.g736
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bile acid structure on bile flow and biliary lipid secretion in the hamster

Abstract: A comprehensive study of the influence of bile acid structure on bile flow and biliary lipid secretion was carried out by infusing pure bile acids at a physiological rate into the proximal small intestine of a bile fistula hamster. Twelve individual bile acids, cholate (C), ursocholate (UC), chenodeoxycholate (CDC), and ursodeoxycholate (UDC) as their glycine (G), taurine (T), or unconjugated form, were studied so that influence of the hydroxy substituents as well as side-chain structure could be defined. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 0 publications
6
67
1
Order By: Relevance
“…There is roughly a linear correlation between biliary bile acid and lipid secretion. 5 Thus, a doubling of TC flux through the canalicular membrane is consistent with the observed almost 2-fold increase in TC-dependent biliary secretion of cholesterol and phospholipid following secretin (Fig. 6).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There is roughly a linear correlation between biliary bile acid and lipid secretion. 5 Thus, a doubling of TC flux through the canalicular membrane is consistent with the observed almost 2-fold increase in TC-dependent biliary secretion of cholesterol and phospholipid following secretin (Fig. 6).…”
Section: Discussionsupporting
confidence: 86%
“…4 Multiple passes of bile acids through the canalicular membrane leads to an increased bile acid biliary transit time, increased choleretic efficiency of bile acids (e.g., increased bile flow for each bile acid molecule secreted), and increased biliary lipid secretion. 5 We have characterized the transport activity of the apical Na Ï© -dependent bile acid transporter (ASBT) originally described in the ileum in isolated rat cholangio-cytes. 6 In addition, we have shown with immunofluorescence studies that ASBT is present in the apical membrane of large cholangiocytes and large (greater than 15 m in diameter) isolated intrahepatic bile duct units.…”
mentioning
confidence: 99%
“…It has been reported that NaTC induces greater secretion of phospholipids and cholesterol than NaGC in hamsters. 26 The features of the PC and cholesterol secretion from HEK/ABCB4 cells were consistent with this observation.…”
Section: Expression Of Human Abcb4 In Hek293 Cellssupporting
confidence: 80%
“…A parameter that reflects the efficacy of bile acids to induce biliary lipid secretion is the (phospho-) bile flow and biliary phospholipid and cholesterol secretion rates decrease upon interruption of the enterohepatic circula-lipid-to-bile acid molar ratio. 28,37,38 Data presented in Fig. 3, however, indicate that a clear-cut relationship was not obtion by 54 { 14%, 74 { 13%, and 64 { 8%, respectively, parallel to the decrease in bile acid secretion rate (092 { served in any of the models between the phospholipid-to-bile acid molar ratio and the APF secretion rate.…”
Section: Inhibition Of Biliary Lipid Secretion By Sulfated Lithocholymentioning
confidence: 92%